Pengaruh Manajemen Risiko Kredit Terhadap Kinerja PT Bank Perkreditan Rakyat Sumatera Selatan - M. Alfan Nurrachman; Faitullah Faitullah (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
The effect of credit risk management on the performance of PT Bank Perkreditan Rakyat South Sumatra for the period 2015 - 2019. The problem formulation in this study is how the effect of credit risk management on the performance of PT Bank Perkreditan Rakyat South Sumatra. This study aims to determine the effect of credit risk management on the performance of PT Bank Perkreditan Rakyat South Sumatra. The research method uses quantitative methods. The data analysis method used is descriptive. Based on the results of the study, it shows that the effect of credit risk management on the performance of PT Bank Perkreditan Rakyat South Sumatra for the period 2015 - 2019 as measured through PPAP shows that PPAP has an effect on BPR income, namely in 2015 - 2017 with the increase in PPAP, the income is reduced and in 2018 - 2019 with decreasing PPAP, income increases.